2012
DOI: 10.3389/fphys.2012.00401
|View full text |Cite
|
Sign up to set email alerts
|

Outlook: membrane junctions enable the metabolic trapping of fatty acids by intracellular acyl-CoA synthetases

Abstract: The mechanism of fatty acid uptake is of high interest for basic research and clinical interventions. Recently, we showed that mammalian long chain fatty acyl-CoA synthetases (ACS) are not only essential enzymes for lipid metabolism but are also involved in cellular fatty acid uptake. Overexpression, RNAi depletion or hormonal stimulation of ACS enzymes lead to corresponding changes of fatty acid uptake. Remarkably, ACS are not localized to the plasma membrane where fatty acids are entering the cell, but are f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
1
20
0
1
Order By: Relevance
“…After excluding the possibilities of impaired Mtp activity and exaggerated FA uptake, we found that enterocytes overexpressing Lxra show increased acsl3a transcript abundance, and that the encoded protein's forced expression is suffi cient to recapitulate, in part, the phenotype of Tg ( fabp2:EGFP-nr1h3 ) transgenic animals. Of course, other Lxr effectors acting in the intestine may contribute to the global control of lipid traffi cking; however, our work demonstrates that, among the myriad regulatory events governing lipid droplet biogenesis, site-specifi c activation of fatty acyl-CoA represents a mechanism for funneling these metabolites to storage ( 28,29,55,57 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…After excluding the possibilities of impaired Mtp activity and exaggerated FA uptake, we found that enterocytes overexpressing Lxra show increased acsl3a transcript abundance, and that the encoded protein's forced expression is suffi cient to recapitulate, in part, the phenotype of Tg ( fabp2:EGFP-nr1h3 ) transgenic animals. Of course, other Lxr effectors acting in the intestine may contribute to the global control of lipid traffi cking; however, our work demonstrates that, among the myriad regulatory events governing lipid droplet biogenesis, site-specifi c activation of fatty acyl-CoA represents a mechanism for funneling these metabolites to storage ( 28,29,55,57 ).…”
Section: Discussionmentioning
confidence: 91%
“…Acsl3 targeting to cytoplasmic lipid droplets is achieved by an N-terminal cytoplasmic lipid droplet anchor motif that is not present in other Acsl family members ( 28 ) This enzyme acts throughout lipid droplet biogenesis to activate CoA thioesters for subsequent incorporation into the growing storage depot ( 29 ). The induction of the encoding acls3a transcript raised the possibility that this enzyme might serve to activate FAs for incorporation into glycerolipids and cholesteryl esters at the surface of lipid droplets, "channeling" them away from incorporation into chylomicrons ( 56,57 ).…”
Section: Intestinal Overexpression Of Lxra Delays Lipid Absorptionmentioning
confidence: 99%
“…It has been variously speculated that FA entry might occur via junctions between the plasma membrane and the endoplasmic reticulum (ER). Alternatively, entry may be mediated by fatty acid binding protein (FABP) isoforms (47), or facilitated by the FA transport proteins (FATP/ACSVL) (52) that are themselves acyl-CoA synthetases. Several groups, however, have shown that the directionality of FA entry or “vectorial transport” is driven by the intracellular metabolism of the FAs (4, 47, 122).…”
Section: Fatty Acid Use By Acyl-coa Synthetasesmentioning
confidence: 99%
“…Alternatively, studies of FA uptake may be an exception to the idea that location dictates function, because changing the expression level of intracellular ACSLs or FATPs alters cellular FA retention (47, 133, 207). In 3T3-L1 cells, for example, overexpressing FATP1 or FATP4 on the ER or overexpressing ACSL1 on the mitochondria increases FA uptake and retention by 40% (207).…”
Section: Acyl-coa Synthetases and Fatty Acid Transport Proteinsmentioning
confidence: 99%
“…Acyl CoA synthetase-1 (ACSL1), a protein reported to be localized at mitochondrial and endoplasmic reticular membranes, has been hypothesized to remotely affect LCFA uptake in mouse hearts, hepatocytes, adipocytes, epithelial cells, and E. coli through vectorial acylation as part of the mechanism “metabolic trapping” [7-15]. Despite the importance of ACSL1 in initiating intracellular lipid usage, the impact of ACSL1 on active fatty acid uptake rates and the consequences of altered uptake on cellular lipid utilization in the heart are not understood.…”
Section: Introductionmentioning
confidence: 99%